Gaseous and particulate polycyclic aromatic hydrocarbons at the Gosan background site in East Asia - Kim, J. Y.; Lee, J. Y.; Choi, S. -D.; Kim, Y. P.; Ghim, Y. S. (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
The seasonal intensive field measurements of gaseous and particulate polycyclic aromatic hydrocarbons (PAHs) were carried out at the Gosan international background site from November 2001 to August 2003. The annual average concentrations of gaseous and particulate PAHs are 1.4 ng m(-3) and 2.9 ng m(-3) (Sigma(14)PAH), respectively. Distinct seasonal variations exist with the highest concentration in winter and the lowest concentration in summer. In comparison with other places in Korea and other countries, the most distinguishing features at Gosan are the significantly low concentrations of low-molecular weight gaseous PAHs. In addition, noticeably high particulate PAH concentrations measured at urban and background areas in Korea could represent the regional characteristics of East Asia under the influence of high emission from China. The BaP equivalent concentrations (BaPeq) at Gosan, which are based on the US EPA's toxicity equivalency factors for carcinogenic PAHs, are much higher than those at coastal or background sites in USA and Europe, and even comparable with that at urban sites in Europe. The possibility of more aged PAHs in the atmosphere associated with the long range transport of PAHs during winter period was suggested. It was found that larger fraction of non-exchangeable PAHs had strong influence to the gas/particle partitioning of PAHs at Gosan. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: BIOMASS BURNING CONTRIBUTION; LONG-RANGE TRANSPORT; ORGANIC-COMPOUNDS; SOURCE APPORTIONMENT; ATMOSPHERIC-DEPOSITION; CARBONACEOUS PARTICLES; COASTAL ATMOSPHERE; ADJACENT COASTAL; DRY DEPOSITION; PAHS